Effect of the addition of nano carbon black on the interfacial reactions in the short carbon fiber reinforced SiC-BN-ZrC-ZrB2 composites. (October 2022) - Zhang, Pengfei; Yang, Guangchao; Zhang, Lingfeng; Yu, Renhong; Ma, Jingling; Yang, Bin; An, Shizhong; Pang, Bo
Highlights: Oxide film and impurities in raw powders still react with carbon fiber. SiC powder reacts with carbon fiber to form strong interfacial bonding force. ZrC powder leads to strong restriction and corrosion to carbon fiber. ZrB2 powder causes extremely severe corrosion and destruction to carbon fiber. Nano carbon black powder cannot prevent the interfacial reactions. Abstract: Interfacial reactions and their control are crucial for improving the performance of short carbon fiber (Csf ) reinforced SiC-BN-ZrC-ZrB2 composites. To clarify whether nano carbon black (NCB) could prevent these reactions, Csf /SiC–NCB, Csf /BN–NCB, Csf /ZrC–NCB and Csf /ZrB2 –NCB composites with a carbon black content of 10 vol.% were prepared and carefully studied in the present work. Results showed that the oxide film and impurities in raw powders still reacted with carbon fibers during the hot pressing process. SiO2 reacts with carbon fibers to form strong interfacial bonding force. B2 O3 does not react with carbon fibers at the present conditions. ZrO2 in ZrC powder leads to strong restriction and serious corrosion to carbon fibers. ZrC lattice is easily decarbonized, resulting in a decrease in its interplanar spacing. ZrB2 together with its oxide film causes extremely severe corrosion and complete structural destruction to carbon fibers. Nano carbon black cannot prevent these interfacial reactions, but it reacts with impurities to form carbides. Graphical abstract: Image, graphical abstract